HOSPITAL NURSE TURNOVER INTENTION : THE ROLE OF WORK STRESS AND WORKLOAD WITH JOB SATISFACTION AS MEDIATION - Almubarokah, Nudia Bakah; Bagis, Fatmah; Endratno, Hermin; Rahmawati, Ika Yustina (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study examines work stress and workload on nurse turnover intention, including the mediating factor of job satisfaction in type c hospital nurses in Purwokerto. This research was conducted on type c hospital nurses in Purwokerto, as many as 127 respondents out of 185 nurses, between December 2023-January 2024. The sampling technique used was convenience sampling, by setting quotas only as much as possible in each hospital. As a result, 127 respondents were collected from the sampling, including 31 male nurses, and 96 female nurses with a dominant age of 26-30 years. The results of the calculation analysis prove that Job Stress, Workload and Job Satisfaction have a positive but insignificant effect on Turnover Intention. Job Stress has a positive and insignificant effect on Job Satisfaction. Workload has a positive but insignificant effect on turnover intention. Mediation results show that Job Satisfaction cannot mediate the relationship between job stress and workload on turnover intention. The results of this study indicate that excessive stress and burden will reduce satisfaction at work, but cannot significantly reduce turnover intention. Keywords: Work Stress, Workload, Job Satisfaction, Turnover Intention